The Concept of Religion in the Fiction of Intizar Hussain - Dilbar, Fareeha; Qandeel, Bazghah (sourcecoder, 2024)
Intizar Hussain is one of the famous fiction writer of narrative literature۔You are a multi-talented literary personality. A glimpse of religious thoughts in Intisar Hussain. It is a Natural Thing that religious thoughts come up again and again. While living in the society, a person is bound many types of restriction ,be it social references, or ideology and religion ,he has to go thought the bitter experience of migration, in his stories, the power Seems to be influenced by the use of religious references and Dev Mala, Quranic legends, Bible, Old Testament Band and Sanimat, Buddha Stories have been describe in wonderful way by him۔In religious Values the image of life and the existence of man in the image of life ,the purpose of human and the social role of man in the image of life ۔So far Nine collection of his fiction have been published ,the themes which are different from each other, he was awarded the Sitara Imtiaz by the Government of Pakistan, and the highest literary honor of Pakistan ,the kamal fan award by Academy of literature Pakistan.